Analysis Of Factors Influencing The Use Of Contraception And Fertility Devices In Kubu District, Karangasem District - Ni Kadek Intan Rahayu; I Ketut Sudibia (International Journal of Economics and Management Sciences, 2024)
The population problem faced by developing countries to date is the birth or fertility rate which is increasing every year. The use of contraceptives is one of the family planning programs implemented by the BKKBN to control fertility levels and suppress population growth. The objectives of this research are 1) To analyze the influence of education level, employment status, patriarchal culture, and family income on the use of contraceptives in Kubu District, Karangasem Regency. 2) To analyze the influence of education level, employment status, patriarchal culture, family income, and use of contraceptives on fertility in Kubu District, Karangasem Regency. 3) To analyze the indirect influence of education level, employment status, patriarchal culture, and family income to Fertility levels through the use of contraceptives in Kubu District, Regency Karangasem. The analysis techniques used in this research are descriptive analysis techniques and path analysis. The data used is primary data totaling 123 samples. The results of this research show that 1) level of education, employment status, and family income have a positive and significant influence on the use of contraceptives in Kubu District, Karangasem Regency. 2) patriarchal culture has a negative and significant effect on the use of contraceptives in Kubu District, Karangasem Regency. 3) education level, employment status, family income and use of contraceptives have a negative and significant effect on fertility in Kubu District, Karangasem Regency. 4) patriarchal culture has a positive and significant influence on fertility in Kubu District, Karangasem Regency. 5) the use of contraceptives has a direct effect in mediating employment status on fertility in Kubu District, Karangasem Regency.